2007
DOI: 10.1124/jpet.106.116806
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Sodium- and Chloride-Dependent Opioid Peptide Transport System by Small Nonopioid Peptides and Free Amino Acids

Abstract: We recently identified a novel opioid peptide transport system in the retinal pigment epithelium that transports opioid peptides by a Na ϩ /Cl Ϫ -dependent process. Here we describe a similar transport system expressed in SK-N-SH cells (a human neuronal cell line) and show for the first time that the activity of the transport system is modulated differentially by lysine and small nonopioid peptides. The transport process in SK-N-SH cells, monitored with deltorphin II as the substrate, is Na ϩ /Cl Ϫ -dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Currently, the only feature that distinguishes between SOPT1 and SOPT2 is the differential effects of dipeptides and tripeptides. SOPT1 is stimulated by several dipeptides and tripeptides, whereas SOPT2 is inhibited by the same small peptides (1,2,24,30). None of these peptides, however, is a transportable substrate for SOPT1 and SOPT2.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Currently, the only feature that distinguishes between SOPT1 and SOPT2 is the differential effects of dipeptides and tripeptides. SOPT1 is stimulated by several dipeptides and tripeptides, whereas SOPT2 is inhibited by the same small peptides (1,2,24,30). None of these peptides, however, is a transportable substrate for SOPT1 and SOPT2.…”
mentioning
confidence: 90%
“…Accordingly, we named these transporters sodium-coupled oligopeptide transporter (SOPT)1 and SOPT2 (1,2). SOPT1 and SOPT2 transport a variety of endogenous opioid peptides, exogenous peptides such as Tat 47-57 [a fragment of the Tat protein encoded by human immunodeficiency virus (HIV)-1], and synthetic opioid peptides (1,2,17,24). Currently, the only feature that distinguishes between SOPT1 and SOPT2 is the differential effects of dipeptides and tripeptides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both transporters have overlapping substrate specificity and can recognize an array of both endogenous as well as synthetic peptides regardless of their amino acid sequence. 14,[16][17][18] Substrate selectivity studies have revealed that SOPT1 and SOPT2 accept oligopeptides consisting of five or more amino acids. 14,[16][17][18] We wished to study whether a-crystallin mini-chaperones elicit antiapoptotic properties that were shown previously to be associated with parent proteins.…”
mentioning
confidence: 99%
“…14,[16][17][18] Substrate selectivity studies have revealed that SOPT1 and SOPT2 accept oligopeptides consisting of five or more amino acids. 14,[16][17][18] We wished to study whether a-crystallin mini-chaperones elicit antiapoptotic properties that were shown previously to be associated with parent proteins. Secondly, we also wished to determine the mechanisms of uptake of these a-crystallin mini-chaperones in human RPE cells and to characterize the putative oligopeptide transporter(s).…”
mentioning
confidence: 99%